Isolation and partial characterization of the Drosophila alcohol dehydrogenase gene. - Goldberg, D A (1980)
The alcohol dehydrogenase (ADH; alcohol: NAD+ oxidoreductase, EC 1.1.1.1) gene (Adh) of Drosophila melanogaster was isolated by utilizing a mutant strain in which the Adh locus is deleted. Adult RNA from wild-type flies was enriched in ADH sequences by gel electrophoresis and then used to prepare labeled cDNA for screening a bacteriophage lambda library of genomic Drosophila DNA. Of the clones that hybridized in the initial screen, one clone was identified that hybridized with labeled cDNA prepared from a wild-type Drosophila strain but did not hybridize with cDNA prepared from an Adh deletion strain. This clone was shown to contain ADH structural gene sequences by three criteria: in situ hybridization, in vitro translation of mRNA selected by hybridization to the cloned DNA, and comparison of the ADH protein sequence with a nucleotide sequence derived from the cloned DNA. Comparison of the restriction site maps from clones of three different wild-type Drosophila strains revealed the presence of a 200-nucleotide sequence in one strain that was absent from the other two strains. The ADH mRNA sequences were located within the cloned DNA by hybridization mapping experiments. Two intervening sequences were identified within Adh by S1 nuclease mapping experiments.